Workers compensation in Western Australia: the shifting landscape of workers' rights. - Guthrie R; Barns A (Health Sociology Review, 2008)
In 2004 and 2005 the West Australian Labor Government significantly amended the Workers Compensation and Injury Management Act 1981 (WA) (the Act). These amendments followed over a decade of shifting power plays and uncertainty for the many stakeholders in the system. The significance of these state-based reforms cannot be underestimated, providing a localised example of a broader contestation between the interests of private business and the shifting terrain of industrial citizenship. This article documents the last decade of workers compensation reforms within Western Australia and a summary of changes which ultimately took effect in November 2005. In keeping with the post-modern emphasis on context, this paper locates the Western Australian changes within a broader discussion of the shifting landscape of rights and entitlements engendered through neo-liberal discourse. In particular, as this paper explores, the changes to Western Australian workers compensation policy can be read as a reflection on the way employers, government and the insurance industry interpret and engage with the continuing realignment of worker entitlements.